Commodification Of Islamic Values In The Ads Of "Hijab Fresh" Body Lotion - Asla Eva Setya; Ni Made Ras Amanda Gelgel; Ade Devia Pradipta (INJECT (Interdisciplinary Journal of Communication), 2020)
The development of the advertising world often follows the development of society. The close relationship between human and their religion is one of the factors that influence the packaging and advertising of products and then is wrapped in religious values. Changes and additions to the value of products with values that increase the selling power of the product are called commodification expressed by Mosco. One product advertisement with the commodification of religious values is a fresh hijab body lotion advertisement. This paper will describe how the process of commodification in advertisements through the symbols in the ad. This study is a qualitative study using Peirce's semiotic analysis. The process of commodification occurs through the shifting of the message and the impression given is seen from the clothing used by actors in advertisements, the behavior of actors in accordance with Islamic teachings and messages with words that reinforce advertisements in the form of audio or written on packaging and advertisements in mass media. So through this advertisement it is learned that religious values are often commodified to increase the sale value of a product through the symbols in its advertisements.